CONGESTION CONTROL ALGORITHM FOR MESSAGE ROUTING IN STRUCTURED PEER-TO-PEER NETWORKS - Nghĩa, Nguyễn Đình; Sơn, Nguyễn Hoài (Journal of Computer Science and Cybernetics, 2018)
Many complex applications have been built on the basis of structured peer-to-peer (P2P) networks such as information retrieval systems, file sharing systems, and so on. These applications often have to process a large number of queries quickly and efficiently. When the number of queries to a node exceeds its capacity, a local bottleneck occurs and reduces the information processing of the other nodes in the network. This paper proposes a congestion control algorithm for message routing in structured P2P networks by changing the routing table of nodes in the network to route the packet to the destination without going through the congested node. The performance of proposed method has been evaluated and compared with the conventional Chord protocol. The result shows that our proposed method improves the query success rate significantly while minimizing the number of packets generated during congestion control process